2019
DOI: 10.1177/2325967118825453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Operative Time on Short-Term Adverse Events After Isolated Anterior Cruciate Ligament Reconstruction

Abstract: Background: A longer operative time has been previously recognized as a risk factor for short-term complications after various orthopaedic procedures; however, it has yet to be investigated as an independent risk factor for postoperative complications after anterior cruciate ligament (ACL) reconstruction. Purpose: To identify whether a longer operative time in ACL reconstruction is an independent risk factor for the development of postoperative complications, hospital r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 56 publications
4
40
0
Order By: Relevance
“…The association between a longer operating time and a higher risk of infection has been established in operative procedures in general. 11 Agarwalla and colleagues 1 used data from the American College of Surgeons National Surgical Quality Improvement Program database to show that an increase in operating time in ACLR increased the risk of surgical site infection. A study of the same database, but focusing on knee arthroscopic procedures excluding ACLR, found a linear relationship between an increase in operating time and an increase in surgical site infection and sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…The association between a longer operating time and a higher risk of infection has been established in operative procedures in general. 11 Agarwalla and colleagues 1 used data from the American College of Surgeons National Surgical Quality Improvement Program database to show that an increase in operating time in ACLR increased the risk of surgical site infection. A study of the same database, but focusing on knee arthroscopic procedures excluding ACLR, found a linear relationship between an increase in operating time and an increase in surgical site infection and sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…A linear relationship between operative time and the risk of adverse events after total joint arthroplasty, anterior cruciate ligament reconstruction, anterior cervical diskectomy, and ankle open reduction internal fixation has previously been established. 1,8,17,31 Therefore, identifying incremental increases in operative time as an independent risk factor for complications after arthroscopic rotator cuff repair would emphasize the need for operative efficiency and the significance for surgical planning in this patient population.…”
mentioning
confidence: 99%
“…A recent study evaluating the effect of the duration of ACLR procedures on complications reported that a 15-minute increase in operative time was associated with a higher risk of surgical site infections (relative risk, 1.21; 95% CI: 1.08-1.35; p ¼ 0.001). 7 Therefore, our observed increase in operative duration of resident-assisted ACLR may be insufficient to significantly affect postoperative infection rates.…”
Section: Discussionmentioning
confidence: 83%
“…recently become the subject of close scrutiny due to the reported increase in complication rates association with longer operative times observed in resident-assisted cases. 6,7 Previous studies have used the American College of Surgeons National Surgical Quality Improvement Program (NSQIP) database to assess the impact of resident participation in various orthopaedic procedures on postoperative outcomes, with conflicting results. One analysis of 30,628 orthopaedic surgery cases demonstrated that resident involvement was associated with decreased complications.…”
mentioning
confidence: 99%